2012
DOI: 10.1128/jvi.01113-12
|View full text |Cite
|
Sign up to set email alerts
|

A 205-Nucleotide Deletion in the 3′ Untranslated Region of Avian Leukosis Virus Subgroup J, Currently Emergent in China, Contributes to Its Pathogenicity

Abstract: In the past 5 years, an atypical clinical outbreak of avian leukosis virus subgroup J (ALV-J), which contains a unique 205-nucleotide deletion in its 3= untranslated region (3=UTR), has become epidemic in chickens in China. To determine the role of the 205-nucleotide deletion in the pathogenicity of ALV-J, a pair of viruses were constructed and rescued. The first virus was an ALV-J Chinese isolate (designated HLJ09SH01) containing the 205-nucleotide deletion in its 3=UTR. The second virus was a chimeric clone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 65 publications
3
36
0
Order By: Relevance
“…Coinfection, which may have a more powerful pathogenicity and which brings about more serious economic losses, has become widespread among flocks in China (40). Furthermore, coinfection with different subgroups provides the opportunity for the recombination of ALVs and makes it possible for the emergence of new subgroup viruses, such as ALV-J, with stronger pathogenicity and epidemicity (8,31). Therefore, achieving rapid clinical detection of infection is imperative for the effective control of the spread of ALVs (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coinfection, which may have a more powerful pathogenicity and which brings about more serious economic losses, has become widespread among flocks in China (40). Furthermore, coinfection with different subgroups provides the opportunity for the recombination of ALVs and makes it possible for the emergence of new subgroup viruses, such as ALV-J, with stronger pathogenicity and epidemicity (8,31). Therefore, achieving rapid clinical detection of infection is imperative for the effective control of the spread of ALVs (41).…”
Section: Discussionmentioning
confidence: 99%
“…ALVs are divided into exogenous viruses (ALV-A, -B, -C, -D, and -J) and endogenous viruses (ALV-E) according to sequence differences in their long terminal repeats (LTRs) (23). The gag genes encode Gag (group-specific antigen), the pol genes encode reverse transcriptase and integrase, and the env gene encodes the envelope glycoproteins (2,31). The pol genes show Ͼ96% sequence identity among the exogenous ALVs (32).…”
Section: Discussionmentioning
confidence: 99%
“…The mouse anti-ALV-J gp85 serum was The chicken anti-ALV-J serum was obtained from a chicken infected with ALV-J (HLJ09SH01 strain) [28]. The ELISA results indicated that the identified epitope peptide 134 AEAELRDFI 142 was recognized by both of these antisera (Fig.…”
Section: Reactivity Of the Identified Epitope With Chicken Anti-alv-jmentioning
confidence: 99%
“…IL-6 is a multifunctional cytokine with central roles in immune and inflammatory reactions, as well as in cancer development [20-24]. IL-6 plays an important role in host immune system, wherein it has been considered to facilitate elimination of pathogens during virus-host interactions.…”
Section: Introductionmentioning
confidence: 99%